Phenotypic and molecular heterogeneity in fibrodysplasia ossificans progressiva. - Virdi, A; Shore, E; Oreffo, R; Li, M; Connor, J; Smith, R; Kaplan, F; Triffitt, J (1999)
Fibrodysplasia (myositis) ossificans progressiva (FOP) is an extremely rare inherited disorder in which progressive ossification of major striated muscles, often following injury, is associated with abnormal skeletal patterning. Altered expression of bone morphogenetic proteins may be a contributory cause. To examine this hypothesis, we compared the patterns of expression of bone morphogenetic proteins (BMPs) mRNAs from lymphoblastoid cell lines from two small multigenerational families with autosomal dominant transmission of FOP. Although affected members of both families showed the characteristic phenotype of FOP, one family was more severely affected than the other. Expression of mRNAs for BMP-1, 2, 3, 5, and 6 mRNAs were not detected within the more severely affected family, but BMP-4 mRNA was expressed in affected but not unaffected members of this family. The results of linkage exclusion analysis using a highly polymorphic microsatellite marker near the BMP-4 gene were consistent with linkage of FOP and BMP-4 in this family. Within the less severely affected family, affected and unaffected members showed similar levels of mRNA expression of BMPs 1, 2, 4, and 5, and linkage of FOP to the BMP-4 gene was excluded. It is concluded that clinical, radiographic, and biochemical data in these two families with FOP establish clinical and molecular heterogeneity and also suggest the possibility of genetic heterogeneity.